Application of mathematical model to job scheduling in an oil processing firm in Nigeria (2010)
The job scheduling mathematical model was applied to small scale oil winning processing in this paper with a view to develop a framework for the proper scheduling of jobs (orders) in oil winning processing firm in Nigeria. The problem is addressed by supposing we have (n) customers to be served (where n is large) in what way should customers' older be processed such that the firm's profit is maximized while the customers are not unnecessarily delayed? The paper addressed the problem by using makespan as a measure of performance while the job orders were sequentially scheduled according to order of priority to achieve optimum results. The mean makespan for the CDS heuristic is 35.99, for Al is 36.08 while for the usual traditional serial order (USO) method is 40.91. The average gain with the application of CDS heuristic is 4.962 and for AI is 4.912.The results show that CDS and A1 heuristics are preferred to the usual method of USO. Accordingly, the CDS heuristic followed by A1 heuristic, gives the best makes pan results